Biological therapy for the prevention and treatment of postoperative endoscopic recurrence in Crohn's disease: time for acceptance? - Kotze, Paulo Gustavo (2013)
In most patients, postoperative endoscopic recurrence (PER) occurs 1 year after abdominal resection for Crohn’s disease (CD). Preventing PER is essential for disease control, as most patients develop further clinical and surgical recurrences. Conventional therapy with nitroimidazoles, aminosalicylates, and immunomodulators have limited efficacy for preventing PER. Initial trials with biological therapy (infliximab and adalimumab) showed promising results in preventing PER, and the efficacy of these drugs seems higher than that with conventional therapy. The aim of this review is to outline the results of studies that used infliximab or adalimumab for preventing and treating PER in CD patients. Data with both agents are available, and a few, small prospective trials have shown the efficacy of these drugs in patients with a high risk for recurrence. We believe that, in 2013, biological agents will be better accepted for the prevention PER in CD patients, in addition to the already existing data. Larger trials are still underway, and their results will certainly determine the role of these agents in PER, which develops after bowel resection for CD.